Human Trafficking and Country Borders - DiRienzo, Cassandra (International criminal justice review, 2017)
The primary purpose of this study is to empirically test whether neighboring countries within the Schengen region have similar human trafficking prevalence rates. It is argued that the free flow of persons across borders in the region impacts human trafficking in two ways. First, it lessens many of the transportation challenges and costs faced by human traffickers. Second, it enhances the ability of traffickers to acquire knowledge about neighboring countries in regard to policing, demand for trafficked persons, and terrain, which enables trafficking networks to spread. The Moran Index, a measure of spatial autocorrelation, is used to test the hypothesis using the Global Slavery Index’s proportion of country population living in slavery, a proxy for human trafficking. The Moran Index is significant and positive in the Schengen region, indicating that country neighbors within the region tend to have similar human trafficking prevalence rates. The Moran Index is calculated in other global regions (Africa, Asia, and North and South America) in addition to Schengen border itself, and the index is insignificant in these areas, which offers evidence that the relationship between neighboring countries within the Schengen region is unique. Policy implications of these findings are offered.